Forms of Reasoning in Western and Chinese Philosophy. Issue 1 (5th September 2018) - Forster, Michael N.
Abstract: I would like in this article to make some tentative comparative observations about several sorts of reasoning in Western and Chinese philosophy. I try to say something about three important forms of reasoning: logic, skepticism, and practical reason. In each of these cases one can find strands of Chinese philosophy that are strikingly similar to counterparts in Western philosophy. And while in two of the cases in question (logic and skepticism) the strands involved are less common and less fully developed than their Western counterparts, in the third case (practical reason) they are highly sophisticated and in many ways superior to their Western counterparts.